Developmental psychology without positivistic pretentions: An introduction to the special issue on historical developmental psychology. Issue 6 (2nd November 2017) - Koops, Willem; Kessel, Frank
Abstract: Emphasizing the importance of understanding children and child development as 'cultural inventions', William Kessen urged developmental psychologists to forego 'positivistic dreaming'. The first section of this paper summarizes Kessen's central ideas. In the second section the pretensions of positivism (classical nineteenth century positivism as well as twentieth century neo-positivism) are analyzed. The core critique of positivism is based on Poppers falsificationism and the so-called Positivismusstreit within the Frankfurter Schule. Despite those and related fundamental critiques, anti-positivism (such as Kessen's) does not imply anti-empiricism. One corollary – Although contemporary developmental psychology is dominated by empirical-quantitative approaches, a wider range of philosophical and methodological approaches are called for if the failings of lingering positivism are to avoided. In particular, twenty-first century developmental psychology requires critical thinking about the discipline's foundations and history, along with deep analyses of how childhood and child development, and the field itself, are historically and culturally embedded (as Kessen asserted). Section 4 concludes with several critical notes regarding, e.g., the predominantly Western orientation of historical studies of child development and the need to recognize the unavoidable normative, moral dimension in the study of human development. The final section provides a brief overview of the papers that comprise this special issue on historical developmental psychology.